2021
DOI: 10.1097/aog.0000000000004538
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Maternal Depression, Antidepressant Use During Pregnancy, and Adverse Pregnancy Outcomes

Abstract: Depressive symptoms or a clinical diagnosis of depression during pregnancy are associated with preterm birth and low Apgar scores, even without exposure to antidepressants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 67 publications
1
20
0
Order By: Relevance
“…These findings are included for comparison only. Because general population comparisons do not adjust adequately for confounding, they should not be used as a sole basis for making clinical decisions, see discussion) Study (year) Outcomes N AD type Psychiatric control Sibling control Main findings Kautzky (2022) [ 106 ] PNAS 17 SSRI, SNRI Y N Statistically significant associations with preterm birth (OR = 2.36, 95% CI 1.35–4.15), admission to neonatal intensive care (OR = 2.64, 95% CI 1.58–4.40), respiratory problems (OR = 2.85, 95% CI 1.26–6.43), lower gestational age (MD = −0.36, 95% CI −0.81 to 0.08), and lower 5-minute Apgar score (MD = −0.32, 95% CI −0.54 to −0.11) in untreated maternal depression comparisons Vlenterie (2022) [ 107 ] GA, BW, SGA, Apgar score 215 Any N N In general population comparisons, preterm birth associated with prenatal depression (OR = 1.6, 95% CI 1.2–2.1), untreated prenatal depression (OR = 2.2, 95% CI 1.7–3.0), and prenatal antidepressant use for any indication (OR = 1.4, 95% CI 1.1–1.8) Low (<5) 5-minute Apgar score associated with prenatal depression (OR = 1.5, 95% CI 1.3–1.7), and prenatal antidepressant use for any indication (OR = 1.6, 95% CI 1.1–2.5) but not untreated prenatal depression Preterm birth associated with prenatal SSRI use for depression (OR = 1.6, 95% CI 1.0–2.5) and prenatal SSRI use for any indication (OR = 1.9, 95% CI 1.2–2.8) Low 5-minute Apgar score associated with prenatal SSRI use for any indication (OR = 1.7, 95% CI 1.1–2.8) AD use during pregnancy not associated with low BW or SGA De Vries (2021) [ 108 ] Congenital heart defects a 20 Any N N In general population comparisons, statistically significant association between prenatal AD exposure and congenital heart defects (OR = 1.28, 95% CI 1.17–1.41) Statistically significant associations for SSRIs (OR = 1.25, 95% CI 1.15–1.37), SNRIs (OR = 1.69, 95% CI 1.37–2.10), paroxetine (OR = 1.57, 95% CI 1.20–1.97), fluoxetine (OR = 1.36, 95% CI 1.08–1.72), sertraline (OR = 1.29, 95% CI 1.14–1.45), and bupropion (OR = 1.23, 95% CI 1.01–1.49). TCAs, citalopram, escitalopram, and venlafaxine not associated with an increased risk Leung (2021) [ 109 ...…”
Section: What Types Of Study Are To Be Preferred?mentioning
confidence: 99%
“…These findings are included for comparison only. Because general population comparisons do not adjust adequately for confounding, they should not be used as a sole basis for making clinical decisions, see discussion) Study (year) Outcomes N AD type Psychiatric control Sibling control Main findings Kautzky (2022) [ 106 ] PNAS 17 SSRI, SNRI Y N Statistically significant associations with preterm birth (OR = 2.36, 95% CI 1.35–4.15), admission to neonatal intensive care (OR = 2.64, 95% CI 1.58–4.40), respiratory problems (OR = 2.85, 95% CI 1.26–6.43), lower gestational age (MD = −0.36, 95% CI −0.81 to 0.08), and lower 5-minute Apgar score (MD = −0.32, 95% CI −0.54 to −0.11) in untreated maternal depression comparisons Vlenterie (2022) [ 107 ] GA, BW, SGA, Apgar score 215 Any N N In general population comparisons, preterm birth associated with prenatal depression (OR = 1.6, 95% CI 1.2–2.1), untreated prenatal depression (OR = 2.2, 95% CI 1.7–3.0), and prenatal antidepressant use for any indication (OR = 1.4, 95% CI 1.1–1.8) Low (<5) 5-minute Apgar score associated with prenatal depression (OR = 1.5, 95% CI 1.3–1.7), and prenatal antidepressant use for any indication (OR = 1.6, 95% CI 1.1–2.5) but not untreated prenatal depression Preterm birth associated with prenatal SSRI use for depression (OR = 1.6, 95% CI 1.0–2.5) and prenatal SSRI use for any indication (OR = 1.9, 95% CI 1.2–2.8) Low 5-minute Apgar score associated with prenatal SSRI use for any indication (OR = 1.7, 95% CI 1.1–2.8) AD use during pregnancy not associated with low BW or SGA De Vries (2021) [ 108 ] Congenital heart defects a 20 Any N N In general population comparisons, statistically significant association between prenatal AD exposure and congenital heart defects (OR = 1.28, 95% CI 1.17–1.41) Statistically significant associations for SSRIs (OR = 1.25, 95% CI 1.15–1.37), SNRIs (OR = 1.69, 95% CI 1.37–2.10), paroxetine (OR = 1.57, 95% CI 1.20–1.97), fluoxetine (OR = 1.36, 95% CI 1.08–1.72), sertraline (OR = 1.29, 95% CI 1.14–1.45), and bupropion (OR = 1.23, 95% CI 1.01–1.49). TCAs, citalopram, escitalopram, and venlafaxine not associated with an increased risk Leung (2021) [ 109 ...…”
Section: What Types Of Study Are To Be Preferred?mentioning
confidence: 99%
“…However, newborns born to depressed mothers without antidepressant treatment had comparable odds ratios for low Apgar scores. In another large meta-analysis examining the effects of depression and antidepressant use in pregnancy, low Apgar scores were found particularly with SSRI use (fluoxetine and sertraline) compared to other antidepressant drugs [ 27 ]. In preterm infants, one retrospective study comparing 51 exposed preterm infants from 28 to 36 weeks of gestation with 50 non-exposed matched controls [ 7 ] found that a 1 min Apgar score < 7 was more frequent in the exposed group, and lower Apgar scores were associated with a higher sertraline dose.…”
Section: Discussionmentioning
confidence: 99%
“…Article alerts and targeted searches of journals to identify major studies published in the interim that may affect the conclusions or understanding of the evidence and the related USPSTF recommendation were used as part of ongoing surveillance. The last surveillance was conducted on November 25, 2022, and 1 existing systematic reviews was added to the review …”
Section: Methodsmentioning
confidence: 99%